Performance Analysis On Idle Breeder Game - Wu, Steven; Agung Riyadi (Infoman's : Jurnal Ilmu-ilmu Informatika dan Manajemen, 2023)
The performance analysis is an essential process for evaluating the efficiency and effectiveness of a system or software. This study focused on conducting performance analysis of the mobile game "Idle Breeder" on the Android platform. The analysis specifically examined rendering computation, scripts, physics, animation, garbage collection, global illumination, user interface, and other aspects using Unity Profiler software. The findings of the study revealed that the game performed well in various testing scenarios, providing valuable insights for mobile game developers to optimize their game's performance on the Android platform using Unity Profiler. However, it is important to consider that environmental conditions and hardware factors may also influence overall game performance. This research contributes to the advancement of knowledge in improving the performance of mobile games and encourages further exploration in this area. The results of this study can be useful for game developers, researchers, and practitioners in the field of mobile gaming to enhance the performance of their games and ultimately provide a better gaming experience for users.